Окислительные процессы в двухфазных средах - Греков, С.П.; Зинченко, И.П.; Кошовский, Б.И.; Стариков, Г.П. (Физико-технические проблемы горного производства, 2007)
Запропонована математична модель хемосорбционих процесів в шарі зернистого матеріалу, яка відрізняється розділенням середовища на тверду і газову фази. Показано, що такий підхід дозволяє описати гетерогенну реакцію єдиної константи, не залежну від часу. The mathematical model of the chemisorptions processes in the layer of the discrete material is proposed. This model is noted by division of the medium into solid and gaseous phases. It is shown that such an approach allows to describe the heterogenous reaction by means of the common constant that doesn't depend on time.